Pengelolaan Irigasi Tradisional serta Pengaruhnya Terhadap Pendapatan Petani Padi Sawah Irigasi di Sumatera Selatan - Maya Sari; M. Yazid; Dessy Adriani (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2022)
Many analyzes of rice farming production with irrigation systems have been carried out, but research related to traditional irrigation management is still very rare. This study aims to look at the implementation of traditional irrigation management, analyze the factors of traditional irrigation management and their influence on the income of rice farmers in South Sumatra. The method in this research used a survey. This research used descriptive quantitative analysis and purposive sampling. This research used multistage sampling method or gradual sampling. The first step was determine the irrigation management condition layer (disproportionate stratified random sampling). The second stage of sampling used quota sampling method (non-probability sampling). The total sample farmer respondents in this study amounted to 120 people from four villages who run their farms using traditional irrigation located in Lahat district and Pagaralam city. The villages are Pagaruyung village, Jentian village, Lubuk Buntak village and Pelangkenidai village. Data were analyzed used binary logit model, wald test, and t test. The results showed that the factors that influence the management of traditional irrigation are water distribution, water distribution, irrigation pollution and the role of irrigation institutions, with the coefficient of determination obtained is 0,699 or 69,9 percent. There is a statistically significant difference between the income of sample farmers with good irrigation management conditions and sample farmers with poor irrigation management conditions. The income obtained by farmers in good irrigation management conditions is Rp12.379.972 and Rp10.009.264 for the income of rice farmers with poor irrigation management conditions.